Talent identification and development in an English Premiership rugby union club: the perspectives of players and coaches - Dimundo, F.; Cole, M.; Blagrove, R. C.; Herbison, J. D.; Turnnidge, J.; Till, K.; Vitali, F.; Kelly, A. L. (Frontiers in Sports and Active Living, 2023)
The pathway towards senior professional status in sport is affected by a multitude of factors. An abductive examination of the talent identification and development processes at an English Premiership rugby union (RU) club was undertaken for the present study. Part one examined the perspectives on the selection and development processes of senior academy male players (n = 8), whereas part two explored the perceptions of male coaches (n = 7). A total of three focus groups were used. Three main themes were confirmed by players and coaches: (a) task constraints, (b) performer constraints, and (c) environmental constraints. Specifically, although athletes and coaches believed that performer constraints were highly impactful on players' career in RU, there were inconsistencies surrounding the task and environmental constraints. Despite an indication that three common themes impacted an players path, this preliminary study shows an imbalance in the understanding of some of the key factors perceived to be important for talent progression in the present rugby academy. More research using similar qualitative methods is recommended to better understand the differences in opinions between players and coaches. Meanwhile, practitioners should consider implementing objective and holistic strategies to improve the talent pathway in English RU academies.